TEACHING ENGLISH LANGUAGE TO THE BEGINNERS - Sada, Clary; Wiranto, Irfan Agung (Universitas Tanjungpura, 2024)
his study aims to find out the appropriate method to teach English to the beginners. Also, the finding of this research is for publication in the journal. This study is conducted by using online qualitative survey technique. The subjects of this study were teachers who teach English for beginners in Pontianak and its surrounding. The data were collected by a set of close-ended statements in an online questionnaire and also an online interview. The findings showed that there were various methods that can be applied in teaching English to the beginners, and those methods depend on the students